Engineering and characterization of Hu3A4: A novel humanized antibody with potential as a therapeutic agent against myeloid lineage leukemias - Sisi Li; Zhujun Wang; Xiaoping Guo; Yongmin Tang (Neoplasia: An International Journal for Oncology Research)
Leukemia stem cells (LSCs) play a critical role in the initiation, recurrence, and resistance to treatment of leukemia. Eradicating LSCs is crucial for the complete elimination of the disease. CD45RA is identified as an important marker for LSC subsets in acute myeloid leukemia (AML), providing a strategic target for therapy. In this report, we introduce Hu3A4, an innovative humanized CD45RA antibody devised to target LSCs expressing this antigen. Hu3A4 retains the antigen-recognition ability of its parental antibody while removing sequences from the variable region that could elicit human anti-mouse immune reactions. The modified variable regions of the heavy and light chains were intricately fused with the constant regions of human IgG1 heavy and light chains, respectively, producing a humanized antibody that emulates the structure of natural IgG. Hu3A4 was produced through recombinant expression in Chinese Hamster Ovary (CHO) cells, which ensured stable gene integration. In vitro tests revealed that Hu3A4 could effectively target and lyse the cells. Further, in vivo studies highlighted Hu3A4′s substantial anti-leukemic activity, significantly prolonging survival times in treated animal models compared to controls (P < 0.01). To summarize, Hu3A4 exhibits remarkable bioactivity and offers a promising therapeutic potential for the treatment of leukemia patients. Progressing Hu3A4 through additional preclinical and clinical studies is crucial to validate its efficacy as a therapeutic agent for leukemia.